Cultura e práticas escolares na Escola Agrotécnica Federal de Manus-AM (1979-1993) - Cruz, Naasson Barbosa (Brasil, 2021)
This study is part of the field of History of School Institutions and had as research object the Federal Agrotechnical School of Manaus-AM, with the objective of researching the culture and school practices in the context of 1979 to 1993. based on a qualitative research, being the bibliographical research, documental and the semi-structured interview as data collection methodology. The theoretical support had the contributions of Vinão Frago (1995) and Julia (2001). In this way, we first sought to understand the course of agricultural education throughout the 20th century, then we identified the time-spaces and school subjects, and ended with the analysis of the school practices of a teacher who worked in the researched institution. In this way, we were able to enter the researched institution and get to know a little about its daily life in the period from 1979 to 1993. It is hoped that this dissertation contributes to the unveiling of the history of professional education or of a school institution dedicated to agricultural education, as well as to researchers who intend to investigate about the Federal Agrotechnical School of Manaus-AM. As a result of this research, the e-book, entitled The School-Farm System at the Federal Agrotechnical School of Manaus, was developed as an educational product with the objective of serving as a dialogue for teachers, students, researchers and others interested in knowing a little more about the history of Professional and Technological Education in Amazonas.